THE PRACTICE OF INCLUSIVE EDUCATION FOR CHILDREN WITH DISABILITIES: CURRENT SITUATION AND PROSPECTS - N. Laas (Publishing House of the State University of Management, 2017)
The options for creating inclusive educational space in Russia are presented. Basic provisions effectively implement inclusive of Russia are systemized. The main development challenges the foundations of inclusive education system as one of directions of social protection of invalids in Russia are identified, revealed and analyzed. The opportunities and prospects for further development of general education and social protection of children with disabilities in Russia are justified, taking into account the international experience.